(untitled) (Research, Society and Development, 2025)
The Human Papillomavirus (HPV) is a double-stranded DNA virus, with high-risk subtypes, such as HPV 16 and 18, associated with the development of head and neck squamous cell carcinomas (HNSCC). This study aims to evaluate the influence of Human Papillomaviruses (HPV) 16 and 18 on the development of Head and Neck Squamous Cell Carcinoma, to analyze the relevance of early diagnosis for prognosis, and to present the different types of prevention and treatments described in the literature. This is an integrative literature review, with searches in databases using the descriptors ’’Human papillomavirus 16’’, ’’Human papillomavirus 18’’, and ’’Squamous Cell Carcinoma Of Head and Neck’’. Articles published between 2015 and 2025, in English, Portuguese, and Spanish, addressing the relationship between HPV and HNSCC were included. Including aspects of diagnosis, treatment, and prognosis. After screening and applying exclusion criteria, 11 articles were selected for critical analysis. The studies evidence that infection with HPV 16 and 18 subtypes contributes to the carcinogenesis of HNSCC. HPV-positive tumors present distinct histology, greater sensitivity to radiotherapy and chemotherapy, better survival, and lower recurrence. HPV represents a relevant etiological factor, especially in younger individuals. The understanding of the molecular and clinical differences between HPV-positive and negative tumors reinforces the need for early diagnosis and preventive strategies. Infection with HPV 16 and 18 subtypes plays a determining role in HNSCC, influencing pathogenesis, prognosis, and therapeutic response. Prevention strategies, early detection, and clinical management guided by HPV status are essential for better health outcomes.